Sixty years of political talk shows on RAI: From educating viewers to party-democracy to entertaining them with social television. Issue 1 (1st March 2015) - Novelli, Edoardo
This article retraces the evolution of RAI's show schedule for political talk-shows, a heterogeneous and motley macro-genre of programmes that includes journalistic programmes and debates that recall squares or public places: there is a laid-back atmosphere on a television set where the private and personal side prevails over the public one, creating personal moments within entertainment programmes and satire shows. From the first Tribuna Elettorale/Electoral Forum (1960) up to the recent Ballarò (2002–) or Che Tempo che fa/What's the Weather Like (2003–), the article analyses the production and formal aspects – like formats, staging, scenography, direction – as well as the messages and meaning either directly or indirectly related to the different programmes. The aim of the article is to demonstrate that RAI has played an important role in the education of Italians to the rules of democracy as well in the formalization of the different models of public debate that have taken place over the years. Initially, RAI was subordinate to the needs and requests of the political parties and institutions, thus strengthening them; in a second stage it started to being increasingly more autonomous until it brought about changes both within the rules of the public arena and in its protagonists, moving from an educational role to becoming a form of entertainment; in a third stage it started competing with the political system for the representation of public opinion and legitimizing new ways of political participation and behaviour.